Measuring the Degradation of Aromatic Compounds Using Methylorubrum ‎extorquens Isolated from Oil-Contaminated Soils in Southern Iraq - Maki, ‎ Anwar A.; Al-Taee, Asaad M.R.; Atwan, Zeenah W. (Mesopotamian Journal of Marine Sciences, 2023)
An innovative, inexpensive, and environmentally acceptable approach is to use microbes to degrade hazardous materials to reduce soil pollution. Therefore, the purpose of this study was to identify and assess the performance of bioremediation bacteria in soil located adjacent to oil fields. Soil samples were collected, diluted, and grown on a mineral selective medium supplemented with methanol as the sole carbon source. Based on the phenotypic, biochemical, and molecular characteristics, seven out of fifteen isolates were identified as Methylorubrum extorquens. This isolate displayed a high growth rate on methanol, with optical density values of 1.9 at 1% concentration and 1.8 at 2% concentration. Furthermore, it can grow in crude oil as an energy and carbon source. It exhibited a density of 0.09 after seven days of incubation. To our knowledge, this study is the first to report the ability of Methylorubrum extorquens to grow on crude oil and degrade polycyclic aromatic hydrocarbons at a ratio of 65.69% of (v/v) crude oil 0.5%. Due to its presence in contaminated soils, the isolated strain has potential as a natural biodegradation tool to eliminate contamination in oil-related compounds